INFLUENCE OF BRANCH CONTENT OF ETHYLENE/1- HEXENE METALLOCENE –BASED LLDPE ON ITS MISCIBILITY WITH LDPE: A MOLECULAR DYNAMICS STUDY - Hameed, Tayyab (2020)
The effect of branch content of hexene metallocene linear-low-density polyethylene (m-LLDPE) on its miscibility with low-density polyethylene (LDPE) was studied by molecular dynamics simulation. The branches of m-LLDPE were varied from 10 to 80 branches/ 1000 C, distributed uniformly on the chain. The LDPE was modeled as three long-chain branches with 22 short chain branches of different kinds. m-LLDPE and LDPE were blended at 500K and 450K. The results showed complete miscibility of blends for all the branch contents covered in this study. Lamellar structures in the melts of m-LLDPE and LDPE blends were detected up to a branch content of 40/1000 C.